Pola Kemitraan Dalam Pengembangan dan Pengelolaan Kawasan Perkampungan Budaya Betawi - Laras Ayu Andini; Priyatno Harsasto; Turtiantoro . (Journal of Politic and Government Studies, 2014)
ABSTRACTCultural tourism can be interpreted as a form of Jakarta City Government responsibility in maintaining the sustainability of the local culture especially Betawi culture. Form of the responsible can be seen from the presence of the Betawi Cultural Village. As an industry, tourism requires the involvement of many actors in its management. The participation of the private and the public are not only seen as a booster in building a sustainable tourism but a fair share roles between government, private sector and community involvement in ensuring each actor to create a good service to the public in the tourism sector.This study aims to look at the partnership between government, private sector and communities in the management and development of the Betawi Cultural Village area. In this study, researchers used a qualitative research method with deskripstif approach to collecting data through observation, interviews and documentary studies. This research was conducted at the Department of Tourism and Culture of Jakarta and the Betawi Cultural Village. Interviews were conducted with actors involved in the network of partnerships and competent in their respective fieldsPartnership is a form of joint research agreement between two or more parties which aim to improve the ability of an organization in achieving its objectives. Based on research showing that partnership is created only in the goverment partnership, which is represented by Culture and Tourism Office of Jakarta with related Institution as a representative of Communities without the active involvement of private sector in the network. The role of private limited through the programs without the involvement of Corporate Social Responsibility in the preparation of regional programs. Lack of actor will weaken theperformance of networking, exchange resources become limited and impact on the lack of innovation and effectiveness of the network in program formulation.Strengthening the network is necessary to formulate tourism development policy is more sensible and purposeful. However, if the private sector can not be involved in this travel network, community-based tourism development model needs to be applied seriously for optimal results.